Challenges and Opportunities of Using Adoptive T-Cell Therapy as Part of an HIV Cure Strategy. (15th February 2021) - Zhou, Yuqi; Maldini, Colby R; Jadlowsky, Julie; Riley, James L
Abstract: HIV-infected individuals successfully controlling viral replication via antiretroviral therapy often have a compromised HIV-specific T-cell immune response due to the lack of CD4 T-cell help, viral escape, T-cell exhaustion, and reduction in numbers due to the withdrawal of cognate antigen. A successful HIV cure strategy will likely involve a durable and potent police force that can effectively recognize and eliminate remaining virus that may emerge decades after an individual undergoes an HIV cure regimen. T cells are ideally suited to serve in this role, but given the state of the HIV-specific T-cell response, it is unclear how to best restore HIV-specific T-cell activity prior initiation of a HIV cure strategy. Here, we review several strategies of generating HIV-specific T cells ex vivo that are currently being tested in the clinic and discuss how infused T cells can be part of an HIV cure strategy.